The discriminatory value of the low-dose dexamethasone suppression test in the investigation of paediatric Cushing's syndrome. - Dias, R; Storr, H; Perry, L; Isidori, A; Grossman, AB; Savage, M (2006)
BACKGROUND: Low- and high-dose dexamethasone suppression tests (LDDST, HDDST) are used in the investigation of Cushing's syndrome (CS). In adults with Cushing's disease (CD), cortisol suppression during LDDST predicts suppression during the HDDST. METHODS: We reviewed the results of the LDDST (0.5 mg 6 hourly x 48 h), HDDST (2.0 mg 6 hourly x 48 h) and corticotrophin-releasing hormone (CRH) test in 32 paediatric patients with CS: 24 had CD, 1 ectopic ACTH syndrome, 5 nodular adrenal hyperplasia and 2 adrenocortical tumours. RESULTS: In CD, LDDST suppressed cortisol from 590.7 +/- 168.8 (mean +/- SD) to 333.7 +/- 104.0 nmol/l after 48 h (0 vs. 48 h, p < 0.05; mean suppression, 45.1%; CI (30.8, 59.4%); 16/24 (66%) suppressed >30%; mean suppression 68.1%, CI (58.1, 77.9%)). The HDDST suppressed cortisol from 596.3 +/- 174.5 to 47.1 +/- 94.8 nmol/l after 48 h (0 vs. 48 h, p < 0.05; mean suppression, 93.5%; CI (88.2, 98.8%) with 17/24 (71%) suppressing to <50 nmol/l and 100% to <50% of baseline). In the LDDST, suppression correlated with that during the HDDST (r = +0.45, p < 0.05) with >30% suppression predicting that in the HDDST and hence CD. CRH increased cortisol by +100.3% (CI 62, 138.5%), 22/24 (91.7%) showing a >20% increase. In the other CS pathologies (n = 8) the LDDST induced no significant decrease in cortisol. CONCLUSION: The LDDST was of diagnostic value by discriminating between CD and other CS aetiologies. In our view the HDDST is redundant in the investigation of paediatric CS.